Halal Food Shopping Behavior of Millennials: Evidence in Indonesia - Puspita, Amelia Tri (Islamic Marketing Review, 2023)
The global community is beginning to realize the importance of consuming halal food. The presence of the halal food industry can arouse the enthusiasm of people who want a shopping system that complies with their religious rules. This study aims to examine halal-labeled food shopping behavior of Indonesian millennials through four determinant factors, namely, spirituality, image, trust and satisfaction. In this study, validity and reliability were tested using partial least square (PLS) based on structural equation modeling (SEM). This study proves that spirituality cannot be directly associated with halal-labeled food shopping behavior. On the other hand, spirituality with the mediating variables of trust and satisfaction can predict shopping behavior for halal-labeled food. This research is limited to halal food consumers in Jabodetabek. To get more significant results, further research is recommended to expand the observation area to a national scale.